Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 1968–1986 - Arsenault, Mathieu; Martel, Marcel (Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 2017)
Les gains en matière de soins de santé mentale en français arrivent au compte-goutte entre 1968 et 1986. L'État ontarien agit avec prudence dans ce dossier. Malgré les pressions des individus et de l'Association canadienne-française de l'Ontario, la mise en place de soins de santé mentale en français s'est butée à de nombreux obstacles tels que la pénurie de personnel parlant français, les difficultés à attirer ce personnel et à les inciter à demeurer notamment dans le Nord, les carences du système d'éducation à former des francophones, les hésitations du gouvernement ontarien, mais aussi l'hostilité au fait français.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods.

Enquête sur l’offre active pour les services auxiliaires de santé du Nord-Est de l’Ontario - Bélanger, Roxanne; Mayer-Crittenden, Chantal; Mainguy, Josée; Coutu, Anie (Reflets, 2018)
Au Canada, il existe peu de données décrivant les services auxiliaires de santé en français disponibles dans les communautés francophones en situation minoritaire. L’objectif de cette étude était d’examiner l’accès aux services d’orthophonie, de physiothérapie et d’ergothérapie en français dans le Nord-Est de l’Ontario. Un outil mesurant la disponibilité et l’offre active des services a été créé et validé. Ce dernier a été distribué aux personnes fournissant les services et aux personnes les utilisant afin de déterminer leurs perceptions concernant l’offre de ces services en français, ainsi que l’accessibilité aux services auxiliaires de santé en français. Les résultats ont montré un manque de services en français dans cette région. Mots-clés : situation minoritaire francophone, services auxiliaires de santé, offre active, Nord-Est de l’Ontario, questionnaires

Citoyens de deuxième classe ? Perceptions de la santé et du système de soins chez les francophones du nord-est de l’Ontario - Bernier, Christiane (Francophonies d'Amérique, 2009)
Cette enquête a pour objectif d’analyser les représentations que les francophones vivant en situation minoritaire ont de leur santé et de celle de leur communauté, de même que leurs perceptions des systèmes de soins auxquels ils ont accès, particulièrement lorsqu’ils vivent dans des régions rurales ou éloignées. De type qualitatif, l’enquête a été réalisée dans le nord-est de l’Ontario auprès de 32 francophones provenant de dix villes différentes. Les résultats montrent que le mépris de la langue minoritaire, le manque de services et de considération pour les francophones ainsi que le faible intérêt accordé par le gouvernement aux usagers des régions éloignées sont les pivots autour desquels se construisent l’insécurité et les désillusions par rapport au système de santé de la province.

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

À la recherche d’un service en français dans le Nord-Ouest de l’Ontario - Boulanger Culligan, Denyse (Reflets, 1996)

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Portrait des minorités de langue officielle au Canada : les francophones de l'Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Analytical Paper, 2010)

Access to resources in the community through navigation: Protocol for a mixed-methods feasibility study - Dahrouge, Simone; Gauthier, Alain; Chiocchio, François; Presseau, Justin; Kendall, Claire; Lemonde, M.; Chomienne, Marie-Hélène; Perna, A.; Toal-Sullivan, Darene; Devlin, R. A.; Timony, Patrick; Prud'homme, Denis (JMIR Publications, 2019)
Background: Community-based health and social resources can help individuals with complex health and social needs achieve their health goals. However, there is often inadequate access to these resources due to a lack of physician and patient awareness of available resources and the presence of social barriers that limit an individual’s ability to reach these services. Navigation services, where a person is tasked with helping connect patients to community resources, embedded within primary care may facilitate access and strengthen the continuity of care for patients. Objective: This study aims to describe the protocol to assess whether the implementation of the Access to Resources in the Community (ARC) navigation model (an innovative approach to navigation services) is feasible, including its potential to achieve its intended outcomes, and to assess the viability of the evaluation approach. Methods: The study consists of a single-arm, prospective, explanatory, mixed-methods, pre-post design feasibility study focusing on primary care practice settings with vulnerable populations. Participants include primary care providers and patients. Results: Enrollment is closed with 82 patients. Navigation services have ended for 69 patients. Conclusions: The study of an innovative complex intervention requires an adequate assessment of the feasibility of the intended approach during which the potential challenges of the planned intervention and need for its adaptation may be uncovered. Undertaking a feasibility study of the ARC navigation model from a conceptually clear and methodologically solid protocol will inform on the practicality and acceptability of the approach, demand for the services, ease of implementation, quality of integration of the new services within primary care, and practicality and potential for efficacy prior to initiating a randomized controlled trial.

Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

Pas de problème: Rapport du comité d'action sur les services de santé en langue française, 1976 - Dubois, Jacques (Ministère de la santé, Ontario, 1976)
Ce rapport est le fruit des travaux du Comité d'action sur les services de santé en langue française, institué par le ministère de la Santé de l'Ontario et officialisé par un arrêté-en-conseil approuvé en février 1975. Le titre "Pas de problème" est choisi parce que selon le comité, il "résume assez bien la réponse des resposnables de services de santé qui n'ont pas encore perçu les besoins d'un groupe linguistique minoritaire. Pas de problème. Cette simplification d'une situation pourtant très complexe dénote sans doute l'attitude que rencontre trop souvent la population française de l'Ontario." Après une brève recension d'écrits (majoritairement américains) sur les barrières linguistiques en santé, le rapport fait un état des lieux en Ontario à cette époque et énonce plus d'une centaine de recommandations.

Leçons apprises sur la navigation des services de santé en français - Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagara, Haldimand, Brant (2019)

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

L’accès aux services de santé en français et leur utilisation en contexte francophone minoritaire. Rapport final - Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Les services de santé en français en Ontario: Offre - demande - utilisation - Gagnon-Arpin, Isabelle; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2011)

Les discours sur la santé des organismes franco-ontariens : du rapport Dubois à la cause Montfort - Gilbert, Anne; Kérisit, Michèlle; Dallaire, Christine; Coderre, Cécile; Harvey, Jean (Reflets, 2005)

L’ambition territoriale dans le dossier de la santé en français - Gilbert, Anne; Lefebvre, Marie; Bouchard, Louise (Francophonies d’Amérique, 2010)
Dix ans se sont écoulés depuis le jugement Montfort, qui consacrait l’Hôpital comme une composante essentielle de la vitalité des communautés francophones en situation minoritaire. Jusqu’à quel point cette reconnaissance du droit à un service en français, accessible dans des établissements localisés dans les milieux dans lesquels la minorité évolue, a-t-elle mené à une ambition plus territoriale chez les intervenants francophones ? L’analyse des propos tenus par 38 participants à un exercice de cartographie conceptuelle sur l’avenir des services de santé en français en Ontario révèle qu’ils ne s’aventurent pas très loin sur le terrain des modalités de l’édification d’un véritable territoire francophone en santé. L’institution est évoquée, mais davantage comme un projet appartenant à un horizon lointain que comme un enjeu actuel. En guise de conclusion, les auteures se sont interrogées sur les effets d’une telle vision sur l’avenir des services de santé en français.

Services de santé pour la communauté franco-ontarienne : feuille de route pour une meilleure accessibilité et une plus grande responsabilisation - Groupe de travail sur les services de santé en français (Ministère de la Santé et des Soins de longue durée de l'Ontario, 2005)

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Concordance et discordance linguistique : comprendre l’expérience des patients francophones chez leur médecin de famille dans le Nord de l’Ontario - Jutras, Chloé. F. (Focus sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2017)

Linguistic concordance and discordance: Understanding the Francophone patient experience during a visit to their family physicians' Office in Northern Ontario - Jutras, Chloé F. (Focus on Research [Centre for rural and northern health research], 2017)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

« Nager à contre-courant comme des saumons… » : les défis d’un centre de santé communautaire francophone en Ontario - Entrevue avec Wesley Romulus - Kérisit, Michèle (Reflets, 1995)

Recherche-graphie: Des stages en français pour se préparer à travailler auprès communautés francophones en situation minoritaire - Landry, Simon (Evidence Exchange Network (EENet), Programme de soutien au système provincial (PSSP) au Centre de santé mentale et de toxicomanie (CAMH))
Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire, des stages en milieu francophone ont été offerts à des étudiant.e.s bilingues des universités anglophones. De tels stages pourraient encourager ces nouveaux professionnels en santé à s’afficher comme pouvant s’exprimer enfran çais, même quand ils-elles se trouvent à travailler dans un milieu anglophone.

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Santé mentale - Michel, Isabelle; Lévesque, Johanne (Programme de recherche, d'éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2005)

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Besoins et lacunes en matière de services de santé en français dans l’Est Ontario - Ouellette, Rachel; Mailhot, Renald (Réseau des services de santé en français de l’Est de l’Ontario, 1999)

La santé des francophones à l’aube de l’an 2000 - Picard, Louise; Carrière, Richard; Hébert, Denise (Reflets, 1999)
Neuf articles contenus dans ce numéro spécial sur la danté des francophone à l'aube de l'an 2000 analysent l’état de la santé de la population francophone et décrivent des modèles, des pratiques et des programmes de santé et de promotion de la santé, dont certains innovent au niveau de la formation des professionnels de la santé. Ce numéro de Reflets n’est pas exhaustif, loin s’en faut! Cependant, il se veut un outil de réflexion et un intervenantes dans les domaines qui touchent la santé.

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Préparer le terrain : soins de santé primaires en français en Ontario. Rapport provincial - Réseau francophone de santé du Nord de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario; Réseau des services de santé en français de l’Est de l’Ontario (2006)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)

Des stages en français pour se préparer à travailler auprès communautés francophones en situation minoritaire - Savard, Jacinthe; Benoît, Josée; Dubouloz, Claire-Jehanne; Breau-Godwin, Stéphanie (Reflets, 2018)
Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire (CFSM), des stages en français ont été offerts à des étudiantes et étudiants bilingues de programmes de formation professionnelle offerts en anglais au sein d’universités canadiennes. L’expérience a été positive pour l’ensemble des parties prenantes : stagiaires, éducatrices-cliniciennes et responsables de la formation clinique. Après cette expérience, les stagiaires ont mentionné avoir une meilleure connaissance des défis d’accès aux services rencontrés par les CFSM et se sentir plus en mesure d’offrir des services en français à ces communautés. Mots-clés : stage en français, formation clinique, communautés francophones en situation minoritaire, offre active, réadaptation

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Santé des francophones et utilisation des services de santé dans les Réseaux locaux d’intégration des services de santé d’Érié St.Clair et du Sud-Ouest - Smith, Michaela (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2013)

La satisfaction des patients francophones de l’Est de l’Ontario traités en réadaptation à domicile - Tardif, Charles; Dallaire, Christine (Francophonies d’Amérique, 2010)
L’accès à des services de santé en français est aujourd’hui une des revendications importantes des porte-drapeaux francophones non seulement pour assurer la santé individuelle des francophones mais aussi pour favoriser la vitalité des communautés. Cependant, certains des francophones qui font appel aux soins ou à l’appui des professionnels de la santé demandent des services en français, alors que d’autres sont satisfaits de recevoir des services en anglais. Cette étude s’inspire de l’analyse des discours développée par Michel Foucault pour examiner les discours que reproduisent les francophones qui reçoivent des soins de réadaptation à domicile, en français et/ou en anglais. Des entrevues semi-dirigées ont été effectuées avec 12 patients francophones dans l’Est de l’Ontario. Les participants de l’étude sont de façon générale satisfaits des soins reçus, mais la langue des services ne répond pas nécessairement à leurs attentes. Ce sont évidemment ceux qui ne peuvent s’exprimer en anglais, d’une part, et ceux qui s’affichent fièrement comme francophones, d’autre part, qui préfèrent recevoir des soins en français. Toutefois, ce ne sont pas que les caractéristiques linguistiques et identitaires des patients qui influencent les critères qu’ils jugent prioritaires pour évaluer les soins reçus. En effet, leur façon de concevoir leur rapport vis-à-vis le professionnel de la santé joue aussi sur l’importance qu’ils accordent à la langue des soins.

Access to psychiatrists by French-speaking patients in Ontario hospitals: 2005 to 2013 - Tempier, TempierRaymond; Bouattane, El Mostafa; Hirdes, John P. (Healthcare Management Forum, 2015)
There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ontarians were about one-third as likely to have daily contact with psychiatrists in that time period compared to English-speaking patients. These results were not explained by regional differences. Instead, they point to the possibility that language poses an important barrier to specific and highly specialized mental health services in this province.

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.